Bioclimatic solutions existing in vernacular architecture. Rehabilitation techniques - Ferreira, Débora (2014)
The traditional architecture is founded as a defining element of the identity of a region, and its essence should be preserved and conserved by means of maintenance and recovery actions. Thus, the best solutions and proposals for intervention should be looked for but this doesn’t imply a back to back innovation and at construction progress. This work includes the description of techniques for maintenance and conservation of bioclimatic solutions found and inventoried in the north of the Iberian Peninsula, with special focus on a unique bioclimatic solution known as Sunspace, whose main advantage is to contribute significantly to the improvement of the thermal performance of buildings. It is also important to recover the historical heritage in a sustainable manner, allowing it to become an engine of development for both urban and small rural centres that exist in the periphery of the bigger cities.